Endrede grenseflater i en norsk religionsmodell? - Ulla Schmidt (Religionsvidenskabeligt Tidsskrift, 2015)
In this article I analyse three types of borders in the Norwegian model of religion, as they are expressed in two areas: in the area of constitution and other basic legislation, and in the area of public health care and hospitals. These three types are: 1) the border between the state and the majority church with respect to which I particularly focus on the implications of the recent changes to the Norwegian constitution; 2) between the state and religious and worldview communities; 3) and between the majority church and religious communities. A main conclusion is that these borders follow different patterns and trajectories in the two areas of legislation and health care. In the final section, I discuss this conclusion in the light of Linda Woodhead’s recent contributions to a theory of public religion.